2008
DOI: 10.1111/j.1939-1676.2007.0027.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Erythromycin and Gentamicin on Abomasal Emptying Rate in Suckling Calves

Abstract: Background: Commonly used dosage protocols for antimicrobial agents may alter the rate of gastric emptying. Hypothesis: Parenteral administration of erythromycin increases and gentamicin decreases the rate of abomasal emptying. Animals: Five male Holstein-Friesian calves (8-15 days of age). Methods: Calves received each of the following 4 IM treatments in random order: control, 2 mL of 0.9% NaCl; erythromycin, 8.8 mg/kg; low-dose gentamicin, 4.4 mg/kg; high-dose gentamicin, 6.6 mg/kg. Abomasal emptying rate wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
(91 reference statements)
1
18
0
Order By: Relevance
“…2,7,8 Parenteral administration of erythromycin (10 mg/kg, IM) immediately before surgical correction of abomasal volvulus or left displacement of the abomasum in lactating dairy cattle increases the postsurgical abomasal emptying rate. 2 Erythromycin exerts its effect to accelerate gastric emptying by acting as a motilin-receptor agonist via binding to motilin receptors in the pyloric antrum and proximal portion of the small intestine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,7,8 Parenteral administration of erythromycin (10 mg/kg, IM) immediately before surgical correction of abomasal volvulus or left displacement of the abomasum in lactating dairy cattle increases the postsurgical abomasal emptying rate. 2 Erythromycin exerts its effect to accelerate gastric emptying by acting as a motilin-receptor agonist via binding to motilin receptors in the pyloric antrum and proximal portion of the small intestine.…”
mentioning
confidence: 99%
“…Structure-activity studies 3 them to interact strongly with the motilin receptor: a ring structure (typically a 14-member lactone [cyclic ester] ring), an amino sugar (desosamine) bound at C-5 of the ring in a glycosidic linkage, and a neutral sugar (such as cladinose) bound at C-3 of the ring in a glycosidic linkage. 2,7,8 Parenteral administration of erythromycin (10 mg/kg, IM) immediately before surgical correction of abomasal volvulus or left displacement of the abomasum in lactating dairy cattle increases the postsurgical abomasal emptying rate. 5,6 Parenteral administration of erythromycin at the label dosage for cattle (8.8 mg/kg, IM) causes an immediate increase in abomasal motility and emptying rate in milk-fed calves.…”
mentioning
confidence: 99%
“…An unexpected finding of this study was the minimal effect that oral erythromycin lactobionate (20 mg/kg BW) had on indices of abomasal emptying rate and the total IgG and total protein‐time relationships. Previous studies have consistently demonstrated that IM administration of erythromycin (8.8–10 mg/kg BW) produced a marked prokinetic effect in milk‐fed calves and adult cattle 5, 14, 15, 16, 17, 18, 19. Erythromycin base is not absorbed in preruminant calves when administered orally at 10 mg/kg; this result has been attributed to acid destruction of erythromycin in the abomasum 37.…”
Section: Discussionmentioning
confidence: 99%
“…We were, therefore, interested in determining the effect of potential nonantimicrobial prokinetic agents, such as cisapride and bethanechol, on abomasal emptying rate and AEA in neonatal calves, and in comparing their prokinetic effects to a positive control (erythromycin) and a negative control (0.9% NaCl solution). Erythromycin was selected as the positive control because it is known to be a strong prokinetic agent in milk‐fed calves and adult cattle 14, 15, 16, 17, 18, 19. Cisapride was investigated because it increases the rate of gastrointestinal motility in the cat, dog, and horse 20.…”
mentioning
confidence: 99%
“…However, due to the limited bioavailability of flavonoids and saponins in ruminants, the findings including the low dose of PSM require major attention. Erythromycin, flunixin meglumine and levamisole are examples of medicines of confirmed prokinetic effect (Nouri et al., ; Wittek et al., ; Fazeli, Shomali, Firouzi, & Ghane, ) in addition to the main activity, that is, antibacterial, anti‐inflammatory and anthelminthic, respectively. Their contractile impact towards gut smooth muscle observed in vivo is consistent with our findings obtained from experiments performed on bovine isolated abomasum and duodenum strips (Figures , and ).…”
Section: Discussionmentioning
confidence: 99%